(untitled) (RT. A Journal on Research Policy and Evaluation, 2013)
Abstract While the EU is building an open access infrastructure of archives (e.g., Openaire) and it is trying to implement it in the Horizon 2020 program, the gap between the tools and the human beings – researchers, citizen scientists, students, ordinary people – is still wide. The necessity to dictate open access publishing as a mandate for the EU funded research – ten years after the BOAI - is an obvious symptom of it: there is a chasm between the net and the public use of reason. To escalate the advancement and the reuse of research, we should federate the multitude of already existing open access journals in federal open overlay journals that receive their contents from the member journals and boost it with their aggregation power and their semantic web tools. The article contains both the theoretical basis and the guidelines for a project whose goals are: • making open access journals visible, highly cited and powerful, by federating them into wide disciplinary overlay journals; • avoiding the traps of the “authors pay” open access business model, by exploiting one of the virtue of federalism: the federate journals can remain little and affordable, if they gain visibility from the power of the federal overlay journal aggregating them; • enriching the overlay journals both through semantic annotation tools and by means of open platforms dedicated to host ex post peer review and experts comments; • making the selection and evaluation processes and their resulting data as much as possible public and open, to avoid the pitfalls (e.g., the serials price crisis) experienced by the closed access publishing model. It is about time to free academic publishing from its expensive walled gardens and to put to test the tools that can help us to transform it in one open forest, with one hundred flowers – and one hundred trailblazers.